2011
DOI: 10.1021/jf104711x
|View full text |Cite
|
Sign up to set email alerts
|

Easy Access to Aroma Active Unsaturated γ-Lactones by Addition of Modified Titanium Homoenolate to Aldehydes

Abstract: The homo-Reformatsky reaction, in which a metal homoenolate of an ester is added to an aldehyde, was adapted to produce γ-lactones from unsaturated, enolizable aldehydes. By use of titanium homoenolate, 11 different γ-lactones were synthesized in one step with moderate to good yields from readily available aldehydes. In particular, this procedure allowed the rapid preparation of a series of C(12) unsaturated γ-lactones differing in the position and configuration of the double bond. These reference compounds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…After absorption of 870 mL, the reaction mixture was filtered and concentrated. Bulb-to-bulb distillation afforded 117 in a 96% yield: bp, 73 °C/0.25 mbar; IR, 3412, 3011, 2963, 2933, 2874, 1654, 1462, 1403, 1374, 1309, 1282, 1209, 1079, 1023, 977, 940, 908, 858, 814, 794, 719, 640; 1 H NMR, δ 0.97 (t, J = 7.7 Hz, 3H); 2.05 (quint, J = 7.7 Hz, 2H); 2.28−2.44 (m, 3H); 2.95− 3.01 (m, 2H); 3.61 (dd, J = 4.5, 12.8 Hz, 1H); 3.90 (dd, J = 2.5, 12.8 Hz, 1H); 5.32−5.39 (m, 1H); 5.50−5.58 (m, 1H); 13 C NMR, δ 14.2 (q); 20.7 (t); 29.2 (t); 55.3 (d); 58.2 (d); 61.7 (t); 122.3 (d); 134.9 (d); MS (EI, 70 eV), 142 (0, M +• ); 127 (1); 111 (15); 95 (16); 93 (17); 91 (10); 83 (21); 82 (35); 81 (40); 79 (22); 77 (10); 69 (38); 68 (45); 67 (100); 65 (10); 61 (12); 57 (23); 56 (11); 55 (68); 54 (18); 53 (21); 43 (31); 41 (75); 39 (32).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After absorption of 870 mL, the reaction mixture was filtered and concentrated. Bulb-to-bulb distillation afforded 117 in a 96% yield: bp, 73 °C/0.25 mbar; IR, 3412, 3011, 2963, 2933, 2874, 1654, 1462, 1403, 1374, 1309, 1282, 1209, 1079, 1023, 977, 940, 908, 858, 814, 794, 719, 640; 1 H NMR, δ 0.97 (t, J = 7.7 Hz, 3H); 2.05 (quint, J = 7.7 Hz, 2H); 2.28−2.44 (m, 3H); 2.95− 3.01 (m, 2H); 3.61 (dd, J = 4.5, 12.8 Hz, 1H); 3.90 (dd, J = 2.5, 12.8 Hz, 1H); 5.32−5.39 (m, 1H); 5.50−5.58 (m, 1H); 13 C NMR, δ 14.2 (q); 20.7 (t); 29.2 (t); 55.3 (d); 58.2 (d); 61.7 (t); 122.3 (d); 134.9 (d); MS (EI, 70 eV), 142 (0, M +• ); 127 (1); 111 (15); 95 (16); 93 (17); 91 (10); 83 (21); 82 (35); 81 (40); 79 (22); 77 (10); 69 (38); 68 (45); 67 (100); 65 (10); 61 (12); 57 (23); 56 (11); 55 (68); 54 (18); 53 (21); 43 (31); 41 (75); 39 (32).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…( Z , Z )-3,6-Nonadienal 64 was prepared as described by Frerot et al: MS (EI, 70 eV), m / z (%) 138 (6); 123 (12); 110 (11); 109 (20); 95 (30); 94 (13); 84 (29); 82 (20); 81 (35); 79 (44); 70 (30); 69 (29); 68 (23); 67 (100); 55 (60); 53 (24); 41 (90).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,95,102 Frerot and co-workers have found that a homoaldol and cyclization protocol can generate γ-lactones in one pot. 103 Their scope of lactone products was aroma-active, and the products were evaluated by taste by four expert flavorists at Firmenich SA to determine the compounds' flavor profile.…”
Section: β-Functionalization With Heteroatom−x Electrophilesmentioning
confidence: 99%
“…All these spectral data were in accordance with γ-dodecalactones bearing a double bond in the side chain, namely n -dodecen-4-olides. The addition of titanium enolate to unsaturated aldehydes was used to prepare many dodecen-4-olides . The reference compounds were then used to establish the structure and double bond configuration of the naturally occurring lactones (unknowns 1–6 ) shown in Figure and Table .…”
Section: Resultsmentioning
confidence: 99%